Characterization and Identification of a novel chromosome-encoded metallo-β-lactamase WUS-1 in Myroides albus P34 - Liu, Shuang; Zhang, Lei; Feng, Chunlin; Zhu, Jin; Li, Anqi; Zhao, Jingxuan; Zhang, Yuan; Gao, Mengdi; Shi, Weina; Li, Qiaoling; Zhang, Xueya; Zhang, Hailin; et al. (Frontiers in Microbiology, 2022)
In this study, we identified and characterized a novel chromosomally encoded class B metallo-β-lactamase (MBL) gene designated blaWUS-1 in a carbapenem-resistant isolate Myroides albus P34 isolated from sewage discharged from an animal farm. Comparative analysis of the deduced amino acid sequence revealed that WUS-1 shares the highest amino acid similarities with the function-characterized MBLs MUS-1 (AAN63647.1; 70.73%) and TUS-1 (AAN63648.1; 70.32%). The recombinant carrying blaWUS-1 exhibited increased MICs levels against a number of β-lactam antimicrobials such as carbenicillin, ampicillin and imipenem, and β-lactamase inhibitors (clavulanic acid and tazobactam). The metallo-β-lactamase WUS-1 could also hydrolyze these antimicrobials and the hydrolytic activities could be inhibited by EDTA. Genetic context analysis of blaWUS-1 revealed that no mobile genetic element was found in its surrounding region. The plasmid pMA84474 of Myroides albus P34 harbored 6 resistance genes (blaOXA-347, aadS, blaMYO-1, ereD, sul2 and ermF) within an approximately 17 kb multidrug resistance (MDR) region. These genes, however, were all related to mobile genetic elements.